Inovações em organizações públicas: estudo dos fatores que influenciam um ambiente inovador - Ferreira, Rodrigo de Araújo (2012)
In the last decades, it has been observed a very rapid speed of changes in the economic, political and social context, and consequently, it has becoming necessary for the public organizations to prepare themselves to perform satisfactorily in this background. On this basis, the innovation has becoming an increasingly common theme and it is considered as an important means for the organizations to keep pace with changes in the industry. The innovations in public organizations may be of products/services, processes, as well as organizational, the latter being able to promote a propitious environment to the other types of innovation. The overall purpose of the study is to analyze the innovation environment on public organizations from the perspective of the public managers involved in strategic plans and in institutional agencies and arrangements that are aimed at innovation. In specific, it is intended to analyze the factors that motivate and the ones that influence the innovation in the public environment, identifying the index value and the level of presence assigned to it by the public managers of the State of Minas Gerais; to identify critical points to be prioritized by the innovation policy of the State of Minas Gerais in terms of the influencing factors of the innovation in order to enhance it; analyze the outcome, comparing the notion of the different hierarchical levels of the interviewed public managers (strategic and tactical), in order to identify similarities and differences in their perception on the factors that motivate and influence the innovation in public agencies of the State of Minas Gerais. For such, the following authors were studied: Mulgan e Albury (2003), Borins (2008), Motta (2001), Lam (2005), Damanpour e Evan (1984), Roste e Miles (2005), Jacobi e Pinho (2006), Knox (2002), among others, from which it was possible to systematize the motivating and influencing factors of the innovation. There were investigated some organizations of the State of Minas Gerais Government that were involved in the state’s innovation strategy or plans. It was verified that the level of presence of the motivating factors of the innovation and specially the influencing factors of the innovative environment are generally still low, even though the value attributed to these factors is high in the perception of the interviewees. There was also a difference of views among the respondents – strategic and tactical level managers – , mostly due to the level of presence of the influencing factors of the innovative environment.